Flashcard Games As A Learning Tool : Internalizing The Practical Values Of Pancasila - Aryaning Arya Kresna (Green Publisher Indonesia, 2021)
This paper discusses new possible efforts to internalize the values of Pancasila through a flashcard game. This is because these values can be taught in a fun way through games. Internalization of these values can be done explicitly or implicitly in several aspects of the game, namely the rules of the game, the characters, and the narrative. The discussion begins with a hermeneutic analysis of Pancasila values that will be internalized to the game participants. The method used was hermeneutics as a tool of philosophical analysis to obtain a practical concept of the philosophical values of Pancasila. Furthermore, these practical values will be used in the effort to internalize values through flashcards games. The results of the analysis were simplified so that they can be used as a narrative and reference for the game, as well as a reference for game rules. The conclusion is that the flashcards game can be used as a means of internalizing the values of Pancasila if these values can be comprehensively expressed in the narrative, flow, and rules of the game.